On constant vorticity water flows in the $\unicode[STIX]{x1D6FD}$-plane approximation. (26th February 2019) - Martin, Calin Iulian
Abstract : We consider here three-dimensional water flows in the $\unicode[STIX]{x1D6FD}$ -plane approximation. In a quite general setting we show that the only flow exhibiting a constant vorticity vector is the stationary flow with vanishing velocity field and flat free surface.